Electrocochleography in the diagnosis of third window conditions - Kileny, Paul R.; Cherry, Megan M.; McCaslin, Devin L. (Frontiers in Neurology, 2024)
Superior semicircular canal dehiscence (SSCD) is the best known and most common presentation of so-called "third window conditions".There are a variety of diagnostic measures and tests for this condition in the current literature, including air-bone gap, vestibular-evoked myogenic potentials, and electrocochleography (EcochG). The purpose of this study was to investigate the diagnostic utility of Ecochg and its relationship to air-bone gap in a cohort of patients with confirmed SSCD.We reviewed data from 20 patients (11 females and 9 males, age range 21-78 years) with confirmed unilateral or bilateral superior canal dehiscence. 11 patients had unilateral SSCD and 9 patients had bilateral SSCD as determined by high resolution CT scan. This resulted in the inclusion of twenty-nine ears with superior canal dehiscence and 11 normal ears. Our results indicated that all confirmed SSCD ears presented with an abnormal EcochG SP/AP value and that there was a statistically significant difference between normal and dehiscent ears. There was no statistically significant relationship between air-bone gap and SP/AP ratio in the ears diagnosed with SSCD, nor was there a significant difference between dehiscent and normal ears in terms of air-bone gap at three frequencies. These results are consistent with previous studies showing the diagnostic utility of EcochG for this condition, and the variability of air-bone gap. While an unexpected air-bone gap continues to be a red flag for SSCD, its absence along with the presence of subjective symptoms is a reasonable indicator for further clinical investigation, to include EcochG.